Influence of resorcinol–formaldehyde resin on the formation of alkali titanate fibers. Issue 4 (15th February 2022) - Iuchi, Hirotoshi; Horikawa, Toshihide
Abstract: Nowadays, alkali titanate (ATO) fibers are attracting attention because they can provide a reinforcing as well as a functional effect. In this study, ATO fibers were synthesized by a one-step calcination route without specialized equipment and flux using a resorcinol–formaldehyde (RF) resin. Homogeneous mixing of the RF resin dissolved in water, TiO2, and an alkali source led to a uniform dispersion, and the three-dimensional polymerized RF resin formed a closely structured matrix with TiO2 and the alkali source. By carbonizing the RF resins prepared using K or Na as the alkali source, titanate fibers with lengths greater than 1 mm were formed. Growth mechanisms and crystal structures of the titanate fibers synthesized with and without the RF resin were completely different. Effects of the RF resin on the crystal structure and morphology of the titanate fibers were systematically studied by changing the calcination temperature and molar ratio of TiO2 and alkali source (Li, Na, or K). We found that the RF resin played an essential role in producing a suitable reaction field for fiber growth and controlling the morphology of titanate fibers. Graphical abstract: Image 1 Highlights: Titanate fibers can be easily synthesized by a one-step calcination process. Resorcinol-formaldehyde (RF) resin was applied as a carbon source. RF resin gives significant effects on the growth mechanisms of the fiber. The surface exposed by the decomposition of RFC acts as a reaction field. The exposed surface is also important for uniform fiber formation.